PENENTUAN KEBIJAKAN DEVIDEN: BAGAIMANA RELEVANSI UKURAN PERUSAHAAN, PROFITABILIAS, DAN TATA KELOLA DI ERA PANDEMI - M. Dana Prihadi; Nugraha; Maya Sari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The right policy decisions and dividend payments can maximize the value of thecompany and shareholders. The value of the company is determined by the valueof its own capital and the value of debt. Therefore, the stock price means anincrease in the value of the company. In contrast to the larger dividend paymentscan reduce the company's ability to invest which can lead to a decrease in thecompany's growth rate in the future, this can make the shares go down. Thepurpose of this study is to analyze the relevance of firm size, profitability, andgovernance in dividend policy. This research is divided into five main parts. First,it presents the background of the research. This study uses the Library Research method, namely by approaching the theoriesthat are relevant to the focus of the research carried out. In this section, anassessment of the concepts and theories used is carried out based on the availableliterature, especially from articles in various scientific journals. The LibraryResearch approach is carried out to build a concept or theory that forms the basisof the study in this research.This study concludes that if company size has relevance in dividend policy, large,well-established companies will have easy access to the capital market, while newand small companies will have a lot of difficulty having access to the capitalmarket. Due to the ease of access to the capital market which is quite significantfor its flexibility and ability to obtain larger funds, so that the company is able tohave a higher dividend payout ratio than small companies.